2020
DOI: 10.1007/s10900-020-00920-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Mortality Among COVID-19 Patients: A Meta-Analysis

Abstract: Objectives The main aim of this study was to find the prevalence of mortality among hospitalized COVID-19 infected patients and associated risk factors for death. Methods Three electronic databases including PubMed, Science Direct and Google Scholar were searched to identify relevant cohort studies of COVID-19 disease from January 1, 2020, to August 11, 2020. A random-effects model was used to calculate pooled prevalence rate (PR), risk ratio (RR) and 95% confidence interval (CI) for both effect measures. Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
203
4
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(269 citation statements)
references
References 90 publications
20
203
4
22
Order By: Relevance
“…: [15,23]) probability of entering the ICU if he had none of these comorbidities, yet this risk jumped to 31% (95% C.I. : [20,46]) if he had also CKD, and to 27% in the presence of asthma/COPD (95% C.I. : [19,36]) or of weakened immune system (95% C.I.…”
Section: Results Derived From the Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…: [15,23]) probability of entering the ICU if he had none of these comorbidities, yet this risk jumped to 31% (95% C.I. : [20,46]) if he had also CKD, and to 27% in the presence of asthma/COPD (95% C.I. : [19,36]) or of weakened immune system (95% C.I.…”
Section: Results Derived From the Modelsmentioning
confidence: 99%
“…Most studies in the Middle East region focused on risk factors of mortality [16,17,18,19] among COVID-19 patients and, to our knowledge, very little (including a few papers from subsequent parts of the Jaber Hospital cohort) has been published on factors associated with the risk of ICU admission. More globally, an international meta-analysis showed that higher mortality was strongly associated with increasing age, male gender and the presence of obesity, HT, DM, CVD, and cancer, and with some excess mortality associated with several other comorbidities [20]. Other studies in the Middle East examined the risk of disease severity or of severe complications.…”
Section: Results Derived From the Modelsmentioning
confidence: 99%
“…При сравнении ФР, влиявших на риск летального исхода заболевания, в регистре АКТИВ с аналогичными по влиянию ФР, определенными в метаанализе Noor FM, et al [20], включившем данные 58 исследований с участием 122191 пациентов и в метаанализе Parohan M, et al [21], включившем данные 14 исследований с участием 14909 пациентов (рис. 1), установлено, что существует ряд различий.…”
Section: Discussionunclassified
“…1). Наиболее значительное негативное влияние на прогноз в евроазиатской популяции пациентов с COVID-19 оказывала полиморбидность: наличие 2 и более хронических заболеваний повышало риск смерти в 9,5 раз, тогда как в международном регистре Noor FM, et al [20] только в 2,6 раза.…”
Section: Discussionunclassified
See 1 more Smart Citation